Preliminary study on hydrogen storage for fuel of fuel cell using Fe3Al metal hydride system. (November 2019) - Rohendi, D; Rachmat, A; Syarif, N; Said, M; Amelia, I
Abstract: Fe3Âl alloy for hydrogen storage was successfully synthesized from Fe (70 wt%) and Al (30 wt%) through ball-mill method in 5 hours milling and Ball to Powder Ratio (BPR) 10:1 to produced mechanical alloy. The results was confirmed by XRD diffraction pattern at 2¸ = 44.791° (10) which is characteristic peak of Fe3Al. The material was applied on hydrogen storage to form metal hydride in which at various temperature and pressure. The Fe3Al alloy performance for hydrogen storage for fuel cell application was indicated from the capacity of hydrogen adsorption and the ability to supply hydrogen for fuel cell. Characterization by using SEM-EDX on adsorption used alloy showed that Fe3Al Alloy has homogeneous surface and no cracks revealed. XRD pattern of alloy after being used to adsorb hydrogen showed a typical pattern at 2¸ = 44.667° (11). Based on the results it can be concluded that hydrogen storage capacity increases with increasing temperature and pressure, and the average adsorption capacity were 58%. Hydrogen storage by the metal hydride method has met the storage criteria established by the US Department of Energy (DOE) as clean and efficient urban energy for the future.